Nicotinamide Adenine Dinucleotide-dependent Proline Dehydrogenase in Chlorella - McNamer, Alan D. (1974)
An NAD-linked dehydrogenase from Chlorella pyrenoidosa Chick catalyzing the conversion of l-proline to Δ(1)-pyrroline-5-carboxylic acid was partially purified. Δ(1)-Pyrroline-5-carboxylic acid was identified as the product by co-chromatography of it and its o-aminobenzaldehyde derivative with authentic compounds. The enzyme is NAD and l-proline specific and is not an oxidase; NADP is not inhibitory. The Michaelis constant for NAD is 0.08 mm and for proline is 0.73 mm.